Pengembangan Sistem Aplikasi Pelaporan Masyarakat Berbasis Web di Kabupaten Pekalongan - Richa Amalia Permatasari; Bayu Priyambadha; Achmad Arwan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Public information disclosure is a manifestation of democratization in the management of governance that allows public participation in realizing good governance. In the Office of Communications and Informatics (Kominfo) of Pekalongan Regency, it is done by providing a media that accommodates reports of problems from the citizens in an online form which can be accessed through the website of the Government of Pekalongan Regency. However, the problem is the process of distributing reports to Local Government Agency (OPD) is done manually, so that the delivery and response time tend to be slow, and the citizens do not know the follow-up of the problem conveyed. In addition, there is no assessment of the speed of OPD in answering reports that can be used as a benchmark of the OPD in providing excellent service to the citizens. To solve the problem, the author developed a web-based reporting system to report a problem where people can connect with the OPD correlated with the problem and display performance assessments for each OPD based on the speed of their response to reports submitted by the citizens. The author used waterfall model in developing the software. Based on the testing performed, the unit testing, integration testing, and validation testing result 100% valid in all test cases. And the compatibility testing shows that the system can run well on 86.67% of 13 browser versions.